2016
DOI: 10.1111/cga.12145
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the March of dimes preconception/prenatal family health history questionnaire: The Persian version

Abstract: In recent years, there has been a remarkable gap between rapid advancements in genetic technology and public health practice. Looking at the familial health history may bridge this gap for easier and cheaper diagnosis and prevention of congenital anomalies. The aim of this study was to validate and culturally adapt the March of Dimes Preconception/Prenatal Family Health History Questionnaire for the Iranian population. After obtaining written permission from March of Dimes, the translation-back translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that the accuracy of family physicians in case detection and diagnosis of congenital anomalies in rural areas is more than 98% [9]. We also investigated the occurrence rate (33 percent) of termination in pregnancies with congenital anomalies [10], and association of folic acid consumption and birth defects [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the accuracy of family physicians in case detection and diagnosis of congenital anomalies in rural areas is more than 98% [9]. We also investigated the occurrence rate (33 percent) of termination in pregnancies with congenital anomalies [10], and association of folic acid consumption and birth defects [11].…”
Section: Resultsmentioning
confidence: 99%
“…TRoCA has too seemingly succeeded in relation to its regional objectives: annual prevalence rates have been produced consistently over years [7], geographical comparisons have been made possible by linking the TRoCA with international programmes [1, 2], and TRoCA has provided data for some specific investigations [10, 11], service provision for selected anomalies [8], and created a validated tool for family practitioners for case detection and diagnosis of birth defects [9]. In response to the health care needs of high risk population, TRoCA is implementing control and preventive services for some genetic disorders and anomalies in the region [12].…”
Section: Discussionmentioning
confidence: 99%